PRESSURE EFFECTS ON POLYVINYL ACETATE JOINTS IN HEMP-SHIVE PARTICLEBOARDS – A COMPARATIVE STUDY - Hristodorova, Desislava; Savov, Viktor; Mihailov, Vladimir; Kutova, Galina (Innovation in Woodworking Industry and Engineering design, 2025)
This work presents one of the first systematic, ISO-aligned assessments of PVAc-bonded joints in laboratory-made hemp shive particleboards, benchmarked directly against industrial P2 particleboard under identical processing conditions (adhesive type and spread, surface preparation, and three nominal pressing pressures). By holding all bonding variables constant and varying only the substrate and pressure, the study isolates the effect of the substrate on shear strength. It offers actionable data for furniture construction with emergent hemp-based panels. The key achievement is a consistent approximately 45% increase in PVAc shear strength for hemp shive panels across the tested pressures, with mean values rising from 1.23 to 1.53 N/mm², compared to 0.68 to 0.83 N/mm² for P2 (ISO 6237:2017). This result demonstrates that hemp shive particleboards can deliver markedly stronger adhesive joints without changing adhesive type or application rate, directly supporting their use as a higher-performance alternative in PVAc-bonded furniture assemblies. The observed variability at the highest pressure level highlights a practical optimization window for balancing pressure with adhesive spread and substrate permeability.